Optimalisasi pembelajaran sumber daya alam melalui interaksi keterampilan sains dan pendekatan problem solving - Marniyanti, Marniyanti; Auliyani, Novia; Saajidah, Saajidah; Munirah, Sabrina; Putra, Aminuddin Prahatama; Zaini, Muhammad; Fajeriadi, Hery; Hernawati, Hernawati; Yulinda, Ratna (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Due to non-interactive and boring teaching, many students face difficulties in understanding the concept of natural resources. This research aims to improve the learning process of natural resources through the interaction of science skills and problem solving approach. This learning involves problem solving to encourage students to be more active and understand the material more deeply. The research used the Classroom Action Research (PTK) method implemented in two cycles on grade V elementary school students in South Kalimantan. The research procedure was designed in two cycles, where each cycle consisted of one lesson with an effective duration of four lesson hours, plus additional learning time agreed with the teacher. The results showed a significant improvement in students' concept understanding and problem solving ability from the first cycle to the second cycle. In addition, it was found that teachers' activities in guiding students also improved, although there were still some aspects that needed to be improved. The problem solving approach proved effective in improving student engagement and learning outcomes, as well as encouraging the development of critical and analytical thinking skills. The scientific impact of this study shows that the problem solving approach is generally effective in increasing student engagement in learning, although there are some aspects of guidance that need to be improved by teachers to ensure the sustainability of improved learning outcomes. Based on this research, it can be concluded that the application and problem solving approach in Natural Resources learning can be an effective alternative to improve student learning outcomes.Akibat pengajaran yang tidak interaktif dan membosankan, banyak siswa menghadapi kesulitan untuk memahami konsep sumber daya alam. Penelitian ini bertujuan untuk meningkatkan proses pembelajaran sumber daya alam melalui interaksi keterampilan sains dan pendekatan problem solving. Pembelajaran ini melibatkan problem solving mendorong siswa untuk lebih aktif dan memahami materi secara lebih mendalam. Penelitian menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus pada siswa kelas V SD di Kalimantan Selatan. Prosedur penelitian dirancang dalam dua siklus, di mana setiap siklus terdiri dari satu kali pembelajaran dengan durasi efektif empat jam pelajaran, ditambah waktu belajar tambahan yang disepakati bersama guru. Hasil penelitian menunjukkan peningkatan signifikan dalam pemahaman konsep dan kemampuan pemecahan masalah siswa dari siklus pertama ke siklus kedua. Selain itu, ditemukan bahwa aktivitas guru dalam membimbing siswa turut mengalami peningkatan, meskipun masih terdapat beberapa aspek yang perlu diperbaiki. Pendekatan problem solving terbukti efektif dalam meningkatkan keterlibatan dan hasil belajar siswa, serta mendorong pengembangan keterampilan berpikir kritis dan analitis. Dampak ilmiah dari penelitian ini menunjukkan bahwa pendekatan problem solving secara umum efektif dalam meningkatkan keterlibatan siswa dalam pembelajaran, meskipun ada beberapa aspek bimbingan yang perlu diperbaiki oleh guru untuk memastikan keberlanjutan peningkatan hasil belajar. Berdasarkan penelitian ini dapat disimpulkan bahwa penerapan dan pendekatan problem solving dalam pembelajaran Sumber Daya Alam dapat menjadi alternatif yang efektif untuk meningkatkan hasil belajar siswa.